Hemoparasites and their relation to body condition and plumage coloration of the White-necked thrush (Turdus albicollis). Issue 6 (1st November 2020) - De La Torre, Gabriel Massaccesi; Freitas, Fernando Ferneda; Fratoni, Rafael De Oliveira; Guaraldo, André De Camargo; Dutra, Daniela De Angeli; Braga, M.; Manica, Lilian Tonelli
Abstract : Hemoparasites can affect wild birds in numerous ways, but the role of infection occurrence and intensity on bird physiology and morphology is still little known. Secondary sexual characters such as bird body size and plumage coloration are some of the traits which may indicate individual condition because they are negatively affected by parasites and thus ultimately influence mate choice. In this study, we tested if hemoparasite occurrence and infection intensity are negatively related to morphological traits, immunological stress condition and plumage coloration brightness of the White-necked thrush Turdus albicollis . We captured and banded birds, identified age, took body measurements and took a picture of their ventral surface to calculate throat and collar feather brightness. We prepared blood smears to count leukocytes and to detect hemoparasites, using both microscopy and PCR to amplify haemosporidians' DNA. We detected haemosporidians, microfilaria and Trypanosoma in blood smears. Both microfilaria and haemosporidian intensities were negatively related to body mass, and only the second was related to age. Interestingly, haemosporidians' occurrence positively affected throat brightness. In our study population, parasites (microfilaria and haemosporidians) are likely affecting White-necked thrush health such that infected individuals with higher throat brightness might be tolerant to haemosporidians. In conclusion, our results indicate that body morphometric traits and plumage coloration of the White-necked thrush population can be used as a visual indicator of parasite resistance.